Automatic provisioning of QoS aware OSPF configurations - Sousa, Pedro (2007)
This paper presents a contribution for the development of network management tools able to automatically provide QoS aware routing configurations. In this perspective, a traffic engineering framework able to provide near-optimal OSPF configurations is presented. The devised solution takes into account the multiconstrained QoS demands of a given network domain in order to improve the quality of the OSPF weight setting process. To pursue this objective, this work resorts to Evolutionary Algorithms, which provide OSPF configurations based on a bi-objective function. The proof of concept of the proposed optimization framework resorts to a wide range of simulation studies, clearly showing the effectiveness of the devised mechanisms.